THE UNIVERSITY AND THE DEVELOPMENT OF ITS TEACHERS: SOME NOTES - Maura Morita (Editora da Universidade de Santa Cruz do Sul, 2009)
The objective of this article is to discuss the work of university teachers and their need for pedagogical development within the context of Teacher Education. It brings out reflections on three fundamental axes: the university as an educational institution; university teaching and pedagogical education; and university and teacher development. The first axis stresses the role of the university as a teaching institution that works towards the education and construction of human society. The second deals with the university teachers' need of a pedagogical education focused on teaching quality and competence. The third axis emphasizes that the institutional context where teaching takes place is of extreme importance, stressing the responsibility of the university towards its teachers. Therefore, teachers and institutions need to invest in the pedagogical dimension of teaching and be conscious of their educational responsibilities. Finally, this work points out to the need for the development of educational policies involving all teachers, students and institutions in search for an education of quality and committed to the construction of a more just and human society. Key-words: Teacher education. Pedagogical development. University teaching . Higher education.